Anesthetic Management for Concomitant Correction of Congenital Cardiac Defects and Long "O" Ring Tracheal Stenosis: A Role for Heliox?. Issue 6 (15th March 2018) - Mauron, Sylvain; Longchamp, David; Perez, Marie-Hélène; Prêtre, René; Sandu, Kishore; Di Bernardo, Stefano; Boegli, Yann; Dolci, Mirko
Abstract : We present 2 infants with the rare association of long congenital tracheal stenosis, ventricular septal defect, and pulmonary hypertension. We describe a step-by-step assessment of the patients and the necessary procedures for a successful concomitant repair of both cardiac and tracheal malformations. The use of a helium–oxygen mixture (heliox) for the induction of anesthesia and pre-cardiopulmonary bypass is discussed. Abstract : Supplemental Digital Content is available in the text.